Tracing the Divine Office: On Frames and Patterns in Medieval Latin Psalter Manuscripts - Karin Becker (Sillages Critiques, 2023)
Medieval Latin Psalter manuscripts are closely related to the Liturgy of the Hours and private devotional practices, within which they could be read. The psalms were ideally recited in their entirety within a week, though not continuously from beginning to end, but with interruptions. The Book of Psalms was therefore divided into sections and occasionally single psalms were recited several times. In this respect, access to certain psalms or groups of psalms was particularly important. Unlike modern books, however, medieval Psalter manuscripts usually do not contain page numbers or running titles that would make it easier for the user to find their way through the manuscript. Nevertheless, a closer look reveals other aids that make it possible to find certain sections or highlight individual psalms. In the spirit of Goffman, they can be understood as keys that point to a connection with the potential use of the manuscripts. The aesthetic and content-related keys (or in this case, more appropriately, “patterns”) form a complex visual system through which the manuscript can be made useable for certain practices and through which a specific use is immediately suggested to the viewer. However, the individual patterns and especially the complex systems of visual organisation cannot function if the viewer is not able to link the patterns on the page to the abstract frames (in Goffman’s understanding); on the contrary, it can even be misleading. Focusing on Latin Psalter manuscripts from England, this paper will examine the correlation between visual organisation and the specific use of these manuscripts.